2007
DOI: 10.1007/s10439-006-9244-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow Perfusion Improves Seeding of Tissue Engineering Scaffolds with Different Architectures

Abstract: Engineered bone grafts have been generated in static and dynamic systems by seeding and culturing osteoblastic cells on 3-D scaffolds. Seeding determines initial cellularity and cell spatial distribution throughout the scaffold, and affects cell-matrix interactions. Static seeding often yields low seeding efficiencies and poor cell distributions; thus creating a need for techniques that can improve these parameters. We have evaluated the effect of oscillating flow perfusion on seeding efficiency and spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
102
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 63 publications
8
102
1
3
Order By: Relevance
“…As compared to the methods described in the literature, 4,[6][7][8][9][10][11][12] where the seeding process usually takes hours to days, the present SAW method significantly accelerates the cell seeding process. The fast seeding time also means that multiple drops containing the cells can be successively driven into the scaffold to achieve greater cell loading.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As compared to the methods described in the literature, 4,[6][7][8][9][10][11][12] where the seeding process usually takes hours to days, the present SAW method significantly accelerates the cell seeding process. The fast seeding time also means that multiple drops containing the cells can be successively driven into the scaffold to achieve greater cell loading.…”
Section: Discussionmentioning
confidence: 95%
“…As we mentioned before, there are various cell seeding methods being developed and most of these studies investigate the cell viability and functionality. 4,[6][7][8][9][10][11][12] Undoubtedly, cell viability and functionality are critical to the usefulness of any new technique for tissue engineering. 5 Therefore, in addition to high cell viability, the proliferation and differentiation ability of the treated cells showed no difference from those of the untreated cells, indicating that the SAW has no deleterious effects on the cells' functionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on seeding efficiency by static deposition have reported results ranging from 18% to 85%. 3,4,6,[10][11][12] Static seeding also presents the disadvantage of leading to a nonuniform cell distribution. 3,4,10 Dynamic cell seeding with bioreactors has proven to provide a higher efficiency and more even distribution of cells, 13 more particularly within 3D scaffolds, where perfusion systems were reported to lead to greater efficiency and better cell distribution.…”
mentioning
confidence: 99%